2016
DOI: 10.1016/j.biortech.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic bacterial community structure applying the different co-substrates for reductive decolorization of Alizarin Yellow R

Abstract: h i g h l i g h t sFeeding with glucose obtained higher AYR decolorization efficiency than acetate. Diverse cathodic bacterial communities were observed with different co-substrates. Glucose-fed condition was dominated with Citrobacter, Enterococcus and Alkaliflexus. Acetate-fed condition was dominated with Acinetobacter and Achromobacter. Co-substrate types impacted performance and the cathodic bacterial communities. a r t i c l e i n f o t r a c tSelective enrichment of cathodic bacterial community was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…), azo dyes (Sun et al . ), etc. However, to our best knowledge, this study is the first report on a strain of Delftia with DET‐degrading ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), azo dyes (Sun et al . ), etc. However, to our best knowledge, this study is the first report on a strain of Delftia with DET‐degrading ability.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the Delftia genus were reported to degrade many environmental pollutants, such as aniline (Zhang et al 2008), terephthalate (Shigematsu et al 2003), para-hydroxybenzoate (Patil et al 2006), azo dyes (Sun et al 2016), etc. However, to our best knowledge, this study is the first report on a strain of Delftia with DET-degrading ability.…”
Section: Identification and Characterization Of Strain Wl-3mentioning
confidence: 99%
“…When biocathode was switched from heterotrophic to autotrophic (NaHCO 3 -fed) cultivation without external electron donor, E 24h could still be maintained at 85.0 ± 2.0%, 91.4 ± 1.8% and 84.9 ± 3.1% for PCE, TCE, and 1,2-DCA, respectively. This verified that the cathodic biofilm could utilize electrode as the sole electron donor for CAHs dechlorination and use these electrons to build up a transmembrane electrochemical gradient ( Rabaey and Rozendal, 2010 ; Liang et al, 2014 ; Sun et al, 2016 ). The NaAc- and NaHCO 3 -fed biocathode had the same cathodic potential of −0.26 V and the initial reaction currents of both were similar ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 53%
“…Microbial community analysis indicated that Proteiniphilum (13.18%) and Pseudomonas (12.42%) were the dominant bacterial genera in the cathodic biofilms formed over one year whereas Geobacter (27.37%) and Flavobacterium (10.59%) were most enriched in anodic biofilms (Table 2). Pseudomonas were well known to be exoelectrogenic genus, and the species from Pseudomonas were commonly enriched in anodic biofilms (Nor et al, 2015) and cathodic biofilms (Sun et al, 2016). Proteiniphilum genus was reported to be dominant in the anodic bacterial community in a methane-producing microbial electrolysis cell (Zeppilli et al, 2015), but was found to be the most enriched genus in the present cathodic biofilms.…”
Section: Figmentioning
confidence: 80%